25x2+30x+9 25*9=225 15*15=225 15+15=3025x2+15x+15x+9[5*5xx 3*5x] [3*5x 3*3]5x(5x+3)+3(5x+3)(5x+3)(5x+3)Answer: (5x+3)2
To subtract 7x^3 - 5x^4, you first need to rearrange the terms in descending order of the exponents. So, the expression becomes -5x^4 - 7x^3. Since the terms have different exponents, you cannot directly subtract them. The result is simply -5x^4 - 7x^3.
6x-x+15-9= 6x-x=5x 15-9=6 5x+6=0 5x=-6 x=-1.2
2x plus 5x simplified is 7x.
1.6667
7X^3 Third degree polynomial.
30 + 5x = 15 + 10x 30 = 15 + 5x 15 = 5x x = 3
You can factor a five out of 15 plus 5x. Therefore, 15 plus 5x factors out to 5(3+x). Hope it helps :)
5x + 15 = 5(x + 3)
25x2+30x+9 25*9=225 15*15=225 15+15=3025x2+15x+15x+9[5*5xx 3*5x] [3*5x 3*3]5x(5x+3)+3(5x+3)(5x+3)(5x+3)Answer: (5x+3)2
5x+32+7x+8=180. By the laws of commutativity we can thus say that 12x+40=180. Subtracting 40 we get 12x=140. Divide by 12 and you get x=(do it yourself) This has nothing to do with calculus by the way.
5x+15 = 6x-10 5x-6x = -10-15 -x = -25 x = 25
5x+25=10 5x+25-25=10-25 5x=-15 5x/5=-15/5 x=-3
To subtract 7x^3 - 5x^4, you first need to rearrange the terms in descending order of the exponents. So, the expression becomes -5x^4 - 7x^3. Since the terms have different exponents, you cannot directly subtract them. The result is simply -5x^4 - 7x^3.
If: 10x+7 = 5x+22 Then: 10x-5x = 22-7 And: 5x = 15 So: x = 3
Combining like terms, 16x + 20 = 180 or 16x = 160 so that x = 10
3x + 2x - 20 = 180 5x - 20 = 180 Add 20 to both sides: 5x = 200 Divide both sides by 5: x = 40